Effectiveness of Lomustine Combined With Bevacizumab in Glioblastoma: A Meta-Analysis - Ren, Xing; Ai, Di; Li, Tong; Xia, Lei; Sun, Lingzhi (Frontiers in Neurology, 2021)
Introduction: Despite surgical and chemotherapeutical treatment options, the prognosis for glioblastoma (GBM) remains poor. Some studies have found that using lomustine plus bevacizumab to treat GBM can prolong overall survival (OS) and progression-free survival (PFS). The aim of this study was to explore the efficacy of the two drugs in combination treatment of GBM using a meta-analysis of the existing literature to help settle the ongoing debate. Materials and Methods: PubMed, EMBASE, and the Cochrane Library were searched for the effectiveness of lomustine plus bevacizumab in GBM literature, updated on June 6, 2020. The main outcomes analyzed included PFS and OS; the effects of this drug combination on the 6-month PFS, which represents the percentage of patients who had PFS for 6 months, were also analyzed. All the data were pooled: OS and PFS with the mean difference (MD) and 6-month PFS with the risk ratio (RR). Because there were different control groups and dose groups, two subgroup analyses were run to ensure they were comparable. All statistical analyses were performed using the Review Manager Version 5.3 software. Results: Six clinical trials were identified which included 1,095 patients (treatment group: 516; control group: 579). The group treated with lomustine and bevacizumab showed an improvement in OS (MD =1.37; 95% CI, 0.49–2.25; p = 0.002), PFS (MD = 0.23; 95% CI, 0.13–0.34; p < 0.00001), and 6-month PFS (RR = 2.29; 95% CI, 1.43–3.65; p = 0.0005). Two subgroup analyses of the main outcome, OS, show that the results of Control group A (p = 0.01) and Dose group 2 (p = 0.003) are significantly different from those of the other control or dose groups. Conclusion: This study shows that lomustine and bevacizumab can effectively increase OS, PFS, and 6-month PFS in patients with GBM. The encouraging results of the lomustine and bevacizumab combination therapy for GBM should be studied in more clinical trials in the future.